2012
DOI: 10.2147/prbm.s36389
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristics of social interactions among adolescents in Croatia, Bosnia and Herzegovina, and Macedonia

Abstract: IntroductionThe bioecological model refers to the basic social needs that a person has satisfied through social interactions. In individualist cultures, the need for independence is emphasized with the aim of self-realization and personal achievement. In collectivist cultures, togetherness is encouraged and it prevails over individuality.AimThe aim of this study was to determine whether there were differences in adolescents (n = 1033) from three different cultural environments (Croatia, Bosnia and Herzegovina,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Lastly, we expected culture to influence the content of how awe shapes the small self, namely in terms of the nature of the social networks the individual feels embedded in. Although people in all cultures show a preference for social integration (Baumeister & Leary, 1995; Fiske & Yamamoto, 2005), individuals from collectivist cultures seek security and strong ties with known others, whereas people from individualistic cultures tend to prefer a wider and more loosely connected social network, with ties to strangers as well as intimates (Fiske & Yamamoto, 2005; Klarin, Pororoković, Šašić, & Arnaudova, 2012; Triandis, Bontempo, Villareal, Asai, & Lucca, 1988; Wheeler, Reis, & Bond, 1989). Given these cultural differences (Oyserman et al, 2002), we hypothesized that in collectivistic China, awe would strengthen the intensity of social ties for the individual, whereas in individualistic United States awe will increase the number of people perceived to be part of an individual’s social network.…”
Section: Present Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we expected culture to influence the content of how awe shapes the small self, namely in terms of the nature of the social networks the individual feels embedded in. Although people in all cultures show a preference for social integration (Baumeister & Leary, 1995; Fiske & Yamamoto, 2005), individuals from collectivist cultures seek security and strong ties with known others, whereas people from individualistic cultures tend to prefer a wider and more loosely connected social network, with ties to strangers as well as intimates (Fiske & Yamamoto, 2005; Klarin, Pororoković, Šašić, & Arnaudova, 2012; Triandis, Bontempo, Villareal, Asai, & Lucca, 1988; Wheeler, Reis, & Bond, 1989). Given these cultural differences (Oyserman et al, 2002), we hypothesized that in collectivistic China, awe would strengthen the intensity of social ties for the individual, whereas in individualistic United States awe will increase the number of people perceived to be part of an individual’s social network.…”
Section: Present Investigationmentioning
confidence: 99%
“…Guided by the social functional approach and the universal need for social integration (Baumeister & Leary, 1995; Fiske & Yamamoto, 2005), we expected that awe, by rendering the self smaller, would enhance individuals’ collective orientation in both cultures. Further, given how collectivism is thought to manifest differently in Western and Eastern Asian cultures (Fiske & Yamamoto, 2005; Klarin et al, 2012; Oyserman et al, 2002; Triandis et al, 1988; Wheeler et al, 1989), we expected the content of this orientation to differ in Western and Eastern Asian cultures. For individuals from collectivistic China who seek intimate relation with secure and strong connections, we expected awe to strengthen the intensity of social ties for the individual; whereas for individuals from the individualistic United States who prefers wider and more loosely connected networks, awe was expected to increase the number of people perceived to be part of individual’s social network.…”
Section: Study 5: Awe the Small Self And Embedding In Social Networkmentioning
confidence: 99%
“…It is a common object of interest in many studies on physical activity both in Poland and abroad [8,9,10,11,12,13]. The percentage of students participating in physical activity is very diverse, but still considered low.…”
Section: Introductionmentioning
confidence: 99%
“…In B&H, there is a lower gross domestic product, lower wages, higher unemployment, lower purchasing power, and lower level of education of the population (Statistics Agency of B&H, 2017; Croatian Bureau of Statistics, 2017), which possibly causes a higher level of stress in parents in B&H, and a higher level of negative affectivity in children. Previous research has also shown differences in the expression of collectivist and individualistic orientations among adolescents in these two countries (Klarin et al, 2010;Klarin et al, 2012a;Klarin et al, 2012b;Šimić Šašić & Klarin, 2014;Puhalo, 2005). Previous research has shown that pupils whose families come from collectivist cultures perceive greater teacher proximity (den Brok & Levy, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…The cultural context (macrosystem) influences the development of an individual directly, but also indirectly by influencing the characteristics of significant others (values, attitudes). The characteristics of significant others shape relationships and interactions with children, and affect the characteristics of children (Adams & Ryan, 2005;Darling & Steinberg, 1993 (Klarin et al, 2012b), and their parents have greater influence on decision-making in various spheres of life (Klarin et al, 2010), as well as a greater contribution from family interaction (family satisfaction and family loneliness) to explaining self-esteem (Klarin et al, 2012a). Radin (2002) found a change in value orientations of young people in Croatia towards individualism, as well as differences in value orientations with regard to regional affiliation.…”
Section: The Role Of Cultural Contextmentioning
confidence: 99%